Isolation and characterization of bacteria degrading polychlorinated biphenyls from transformer oil - Rojas-Avelizapa, N G; Rodríguez-Vázquez, R; Martínez-Cruz, J; Esparza-García, F; Montes de Oca-García, A; Ríos-Leal, E; Fernández-Villagómez, G (Folia microbiologica, 1999)
Polychlorinated biphenyls from transformer oil were degraded in liquid culture under aerobic conditions using a mixed bacterial culture isolated from a transformer oil sample with a high content of polychlorinated biphenyls and other hydrocarbons. Four strains were identified, three of them corresponded to genus Bacillus, the other one to Erwinia. Bacteria in the transformer oil could remove as much as 65% of polychlorinated biphenyls (88% W/V in the transformer oil). Additional data showed that the two isolated strains of B. lentus were able to grow on transformer oil and degrade polychlorinated biphenyls by 80 and 83%. Our results provide evidence that microorganisms occurring in transformer oil have the potential to degrade polychlorinated biphenyls.
Keywords: zdravotnické prostředky; elektronika; polychlorované bifenyly; Polychlorinated Biphenyls; Erwinia; Biodegradation, Environmental; biodegradace; Bacterial Typing Techniques; Equipment and Supplies; Bacillus; techniky typizace bakterií; Electronics